1955
DOI: 10.1175/1520-0477-36.10.519
|View full text |Cite
|
Sign up to set email alerts
|

Radar Scope Interpretations of Wind, Hail, and Heavy Rain Storms Between May 27 and June 8, 1954 *

Abstract: Detailed field data and radar observations were studied for a period in which five out of eight storms produced considerable damage. It appears that in many cases the radar offers additional information so that it might be useful in short range forecasting. Certain limitations are noted. Additional data and research are needed before the complete utilization of radar in the detection of severe storms can be established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1958
1958
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Table 4 shows the cells' velocities thus obtained. Now, it is interesting to examine whether precipitation cells are carried or not by the flow at 700 mb level, as stated by several authors (for instance, Stout, 1955). Unfortunately, as the upper wind observations obtained near the rain bands are scanty, the gradient It is seen from While, as the wind velocities in a typhoon are distributed as in Fig.…”
Section: Movements Of Cells In the Rain Bandsmentioning
confidence: 91%
“…Table 4 shows the cells' velocities thus obtained. Now, it is interesting to examine whether precipitation cells are carried or not by the flow at 700 mb level, as stated by several authors (for instance, Stout, 1955). Unfortunately, as the upper wind observations obtained near the rain bands are scanty, the gradient It is seen from While, as the wind velocities in a typhoon are distributed as in Fig.…”
Section: Movements Of Cells In the Rain Bandsmentioning
confidence: 91%
“…The association of high echo speeds (30 to 60 knots) with severely-damaging Nolen, 1959. ) winds, even on occasions with surprisingly low echo tops, is agreed upon by many investigators, for example, Stout and Hiser (1955), Staats and Turrentine (1956), Hiser (1958), Fujita andBrown (1958), andChangnon (1960).…”
Section: Arrangement Andmentioning
confidence: 70%
“…Sudden changes in the protuberances, sometimes occurring within seconds, indicated that the peripheral hail shafts often fall in sudden bursts. Stout and Hiser (1955) also noted a peculiar notched echo shape in a damaging hailstorm, and Sarrica (1958) showed how the long echo fingers moving toward the right of the parent echo motion in an Italian hailstorm were consistent with the fall of small hail (up to 1 cm diameter) in strong shear.…”
Section: Individual Echomentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have discussed-or briefly mentioned-the effects of storm mergers on tornadogenesis (e.g., Stout and Hiser 1955;Bluestein and Parker 1993;Finley et al 2001;Dowell and Bluestein 2002), but few have focused specifically on left-mover-right-mover mergers.…”
Section: Discussionmentioning
confidence: 99%